Assessment of pesticides and ripening chemicals used in selected vegetables at different locations of Bangladesh (Bangladesh Journal of Agricultural Research, 2019)
A survey was conducted in seven districts namely Bogura, Rajshahi, Jashore, Narsingdi, Cumilla, Jamalpur and Gazipur to assess the present status of the usage of pesticides and ripening chemical in major vegetable crops such as tomato, brinjal, country bean and bitter gourd. A total of 280 respondents having 40 respondents from each district were selected randomly for the study. The maximum number of vegetable growers belonged to the age group of 21-40, which is about 50%. About 41% and 25% of farmers accomplished their primary and secondary education in the study areas. Tomato fruit had the highest yield (27.74 tha-1) whereas the highest gross margin was attained from country bean 4,06,832 Tk.ha-1. Almost all of the vegetable growers were used synthetic pesticides (chemical group of Cypermethrin, Emamectin Benzoate, Chlorpyriphos, Carbendazim, Lambda Cyhalothrin, Mencozeb etc.) for protecting their crops from pests and most of them used own hand pump sprayer. Farmers of the study areas applied synthetic pesticides frequently with much higher dosages (8-30 times) than the recommendation. Few farmers practice Integrated Pest Management (IPM) for their crops. Seventy five percent farmers had protective measure during insecticide-pesticide spray and about 40% growers felt uncomfortable after hand spray to the crops. Most of the tomato growers in the study areas (Rajshahi and Jashore) were applied Plant Growth Regulator (PGR)/ripening agents mainly Ethephon @ 2500-8000ppm before 1-3 days of harvest in immature green tomato (1-4 times) for uniform color development to get higher price in the early market. Few traders (10-15%) were applied Ethephon in premature vegetables after harvest. It is strongly recommended to use IPM technology for controlling insects and pest and to create awareness regarding pesticides use practice and safety precautions.Bangladesh J. Agril. Res. 44(2): 261-279, June 2019